2004
DOI: 10.1021/jp0490150
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Nonresonance Raman Scattering from Size- and Morphology-Controlled Gold Nanoparticle Films

Abstract: Gold nanoparticle films with different particles sizes (35 ( 5, 15 ( 1 nm) and agglomerated states were prepared on glass substrates, by salting-out the colloidal solutions with NaClO 4 or NaOH. An ethanol solution of rhodamine 6G was cast on the gold nanoparticle film and the surface-enhanced Raman scattering (SERS) spectrum was measured. We found that the intensity of the SERS signal was higher for the film with larger particles and that the film prepared from NaClO 4 gave higher SERS signals than that prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
112
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(116 citation statements)
references
References 30 publications
2
112
1
1
Order By: Relevance
“…The fabrication of SERS-active substrates has accordingly been a challenge over the decades. [54][55][56] In reality, the enhancement properties of a SERS-active surface are highly susceptible to its method of preparation, and therefore its detailed nanostructure. Lots of SERS-active surfaces currently available are thus lacking in stability and/or reproducibility.…”
Section: Novel Fabrication Of Ag Thin Films For Efficient Sers 3·1 Famentioning
confidence: 99%
“…The fabrication of SERS-active substrates has accordingly been a challenge over the decades. [54][55][56] In reality, the enhancement properties of a SERS-active surface are highly susceptible to its method of preparation, and therefore its detailed nanostructure. Lots of SERS-active surfaces currently available are thus lacking in stability and/or reproducibility.…”
Section: Novel Fabrication Of Ag Thin Films For Efficient Sers 3·1 Famentioning
confidence: 99%
“…29 Alternatively, SERS materials have been made from nanoparticles deposited via electrolyte induced aggregation and sedimentation. 30 Deposits of nanoshells, 31 aggregated nanorods, 32 and other anisotropic nanoparticles 33 have high SERS activity as well. In most cases, however, such nanoparticle layers are disordered and lack long-range periodicity.…”
Section: Orlin Velevmentioning
confidence: 99%
“…Investigations have shown that nanogaps between two or more metal particles are associated with plasmonic "hot spots", and that SERS can greatly increase when the gap distance is reduced; 10,11 that is to say, the SERS signals can be controlled and modulated by electromagnetic field enhancement in interparticle plasmon coupling. Based on this mechanism, many biosensers have been established for the detection of various biomolecules, including peptides, [12][13][14] proteins, [15][16][17][18][19] DNA and RNA, [20][21][22] pathogen, [23][24][25] and living cells.…”
Section: Introductionmentioning
confidence: 99%